Masa Keemasan dan kepemimpinan Kekhalifahan Abu Bakar As Shidiq - Muhammad Bagas Hidayatullah; Wafa Kamila; Aulan; Hudaidah; Tyas Fernanda (Indo Publishing, 2025)
This study examines the golden era and leadership of Caliph Abu Bakr As-Siddiq, the first caliph in Islamic history following the death of Prophet Muhammad (PBUH). The objective of this research is to analyze Abu Bakr’s strategic policies, political challenges, and his contributions in maintaining the unity of the Muslim community and preserving Islamic teachings. This research employs a qualitative descriptive approach using library research based on primary and secondary sources. The findings reveal that Abu Bakr successfully suppressed apostasy movements (Riddah Wars), enforced zakat obligations, confronted false prophets, and initiated the first Islamic expansion toward the Byzantine and Persian territories. Moreover, his initiative to compile the Qur’an represents a monumental legacy that ensured the authenticity of the divine revelation throughout history. In conclusion, Abu Bakr As-Siddiq’s leadership not only preserved the existence of Islam but also laid the foundational framework for an enduring and just Islamic civilization.